Sistem Monitoring Kualitas Air Kolam Ikan Nila - Daniel Sutopo Pamungkas; Amanda Martiza Rayhan; Muhammad Yusuf Al Qadri; Amanda Rafini; suharni, ela ayu (ABEC Indonesia, 2023)
Tilapia is a fish that has high economic value, simply cultivation techniques and affordable princes. In its cultivation, bofloc technology is used and water quality is adequate for tilapia cultivation. Some physical parameters that can be used to determine water quality include acidity (pH), water turbidity (total dissolved solids) and oxygen content in water (do). To ensure the succes of cultivation , breeders must periodically monitor the condition of tilapia ponds with an efficient monitoring tool using 20x4 I2C LCD. In its use, the reading on the sensor from the arduino uno microcontroller will directly display the condition of the biofloc pond water quality level such as the level of pH quality, water turbidity and oxygen content in water which is neededto maximize fish growth.